Neuromechanics of proleg grip-release and strike behavior in caterpillar Manduca sexta - Mukherjee, Ritwika. (Tufts University. Tisch Library., 2021)
Thesis (Ph.D.)--Tufts University, 2020.; Submitted to the Dept. of Biology.; Advisor: Barry Trimmer.; Committee: Barry Trimmer, Eric Tytell, Michael Romero, Mimi Kao, and Jack Gray.; Keywords: Neurosciences, and Biomechanics.; Animals exploit their morphologies to compensate for external forces from their environments to move. Those with skeletal systems have clearly defined degrees of freedom because their muscles work antagonistically around the rigid joints. The translational and rotational degrees of freedom of these structures allow for precisely controlled movements. Conversely, soft animals lack rigid support structures - they bend, fold, wrinkle, and twist with uncontrolled degrees of freedom. Unlike skeletal animals, soft, non-articulated animals are subject to deformation by natural, external forces. This makes soft-bodied movements difficult to predict. How soft animals neuromechanically control their bodies and perform successful behavior is an interesting research question. For my thesis, I studied the neuromechanics of movements in the soft-bodied larvae of the tobacco hornworm, Manduca sexta. To move, the caterpillars rely on segmented muscles controlled by a ventral nerve cord. They also contain a large gut and trachea that maintain consistent tonic pressure in the body. For successful behavior, the neural system must offload some tasks on the mechanical systems — namely the size, shape, and structure of the body. This, ultimately, determines the resultant behavior. I wanted to explore the importance of motoneuronal output in controlling movement in the soft-bodied caterpillar. I studied two distinctly different behaviors of Manduca in detail: the proleg grip-release and the strike response. Despite their different biological scales, the former being limited to a single proleg while the latter requiring the entire body, the neuromechanical findings revealed unexpected similarities between these two movements. The neural data tightly coupled to the timing of the behavior, but the granular details of the neural patterns varied across trials. This suggests that a certain part of the control is embedded in the caterpillar's morphology. The mechanisms by which such soft animals control their movements are expected to reveal useful strategies for designing soft biomimetic robots that have potential applications in medicine, disaster relief, or land exploration. Many bioinspired deformable robots have been designed to emulate certain biomechanical principles of soft animals. Here, I have included a project that developed a soft open-cell tendon-driven foam robot. In both soft robots and soft animals, motor control and the physics of shape change, can help us understand how neural control, the material properties and the morphology of the body work together to determine movement.